Research on the Development of Theme Trends and Changes of Knowledge Structures of Drug Therapy Studies on Major Depressive Disorder Since the 21st Century: A Bibliometric Analysis - Duan, Li; Gao, Yunfeng; Shao, Xiaojun; Tian, ChunSheng; Fu, Chunfeng; Zhu, Gang (Frontiers in Psychiatry, 2020)
Background: Antidepressant treatment is one of the most effective ways of relieving or curing depressive symptoms in patients with major depressive disorder (MDD). Although many studies have explored the efficacy, tolerability, adverse reactions, and functional mechanism of the disease, there has been no systematic evaluation of the relevant results in this field. Aim: This paper aims to analyze the theme trends and knowledge structure of drug therapy studies on MDD since the 21st century by employing bibliometric analysis. Methods: Literature published in PubMed and related to drug therapy studies on MDD were retrieved between 2001 and 2018 in 6-year increments. After extracting major Medical Subject Headings (MeSH) terms/MeSH subheadings, bi-clustering analysis, social network analysis and strategic diagrams were employed to complete bibliometric analysis. Results: Overall, 1,577, 2,680, 2,848 relevant research articles were retrieved for the periods during 2001 to 2006, 2007 to 2012, and 2013 to 2018, respectively. In line with strategic diagrams, the main undeveloped and peripheral theme clusters during 2001–2006 were functional mechanisms of antidepressants in pathophysiology, neuroendocrinology and neural biochemistry. These themes were replaced during 2007–2012 by clinical efficacy and influencing factors of antidepressants with or without psychotherapy, mechanisms of adverse reactions of antidepressants, and predictive studies of clinical therapeutic effects of antidepressants based on brain imaging. During 2013–2018 application and evaluation of new antidepressant agents, early identification and prevention of suicide of patients with MDD, as well as genetic- or bio-markers affecting the response and efficacy of antidepressants were the primary themes. Based on social network analyses, emerging hotspots , such as antidepressive agents, second-generation/adverse effects, depressive disorder, major/metabolism, psychotherapy/methods, and brain/drug effects could be identified during 2007–2012 and 2013–2018. Conclusions: These undeveloped theme clusters and emerging hotspots can be helpful for researchers to clarify the current status of their respective fields and future trends, and to generate novel ideas that may launch new research directions.